Equality of Opportunity and the Expansion of Higher Education in the UK - Vincenzo Carrieri; Apostolos Davillas; Andrew M. Jones (Institute of Labor Economics (IZA), 2021)
Using nine waves of data from Understanding Society (UKHLS), we study the expansion of higher education in the UK, since the landmark Robbins Report in 1963, and its consequences for levels of and inequalities in household income, physical and mental health. We estimate fixed effects models accounting for both cohort and lifecycle effects and use entropy balancing to build a counterfactual scenario that fixes the opportunity set, in terms of the likelihood of being a graduate, at pre-Robbins levels. We confirm that the university expansion was characterised by a large increase in the proportion of graduates, with higher rates of graduation among individuals from more advantaged socioeconomic backgrounds. Having controlled for birth cohort and lifecycle effects, there is evidence of significant inequality of opportunity in the actual outcomes. However, comparing actual outcomes with counterfactual projections, we do not detect an impact of the expansion of higher education on inequality of opportunity (IOp) in income and only small reductions in IOp in physical and mental health.
Keywords: C1; D63; I12; I14; 330; equality of opportunity; higher education; entropy balancing; high dimensional fixed effects; health; income